Women’s Pathways to Incarceration in India and Sri Lanka: Insights From an Intersectional Narrative Analysis - Bhardwaj, Ntasha (Journal of contemporary criminal justice, 2025)
Despite their distinct histories and cultures, India and Sri Lanka often are characterized as reflecting a uniformly patriarchal “South Asian” culture. We draw from a project on women’s pathways to incarceration to interrogate such assumptions. Utilizing narrative life history interviews supplemented with information from life event calendars [LECs], we compare Indian (N = 85) and Sri Lankan (N = 96) women’s accounts of how gender and gender inequality shaped their pathways to incarceration. Women’s stories are framed by divergent criminal-legal system priorities shaped by distinct cultural imperatives: India’s emphasis on family-based dowry-related crimes in contrast with Sri Lanka’s greater concern with women’s morality and “moral” offenses. Women’s narratives of their pathways to incarceration were shaped by these contexts. Despite reporting similar experiences with gender-based violence in the LECs, Indian and Sri Lankan women narrated the meaning of these experiences quite differently. We utilize these distinctions to discuss the intersectional insights that emerge from comparative narrative analyses and call for more international work on gender that is carefully contextually grounded.